2021
DOI: 10.5219/1626
|View full text |Cite
|
Sign up to set email alerts
|

The use of secondary fish raw materials from silver carp in the technology of structuring agents

Abstract: The expediency and prospects of using secondary fish raw materials from silver carp in the structuring agents technology have been substantiated. The combination of secondary fish raw materials and seaweed with different mechanisms of gelation has a targeted effect on the organoleptic, structural-mechanical, and physicochemical properties of food products. Accordingly, the expediency of adding the Black Sea alga cystoseira (2%) to optimize the mineral composition of the structuring agents and increase their je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
(3 reference statements)
0
4
0
1
Order By: Relevance
“…The positive correlations between the "muscle eye" area and the pre-slaughter live weight and carcass weight are also typical for other breeds. In particular, such results were found in Hanvoo bulls [13]. The positive correlation of "muscle eye" with the slaughter weight (of carcass) can be explained by the fact that m. longissimus dorsi presents the two most valuable cuts of the carcass: lumbar and dorsal, which are the significant part of the muscle tissue in the carcass.…”
Section: Resultsmentioning
confidence: 73%
“…The positive correlations between the "muscle eye" area and the pre-slaughter live weight and carcass weight are also typical for other breeds. In particular, such results were found in Hanvoo bulls [13]. The positive correlation of "muscle eye" with the slaughter weight (of carcass) can be explained by the fact that m. longissimus dorsi presents the two most valuable cuts of the carcass: lumbar and dorsal, which are the significant part of the muscle tissue in the carcass.…”
Section: Resultsmentioning
confidence: 73%
“…The absolute speed value of the working container is: (9) The oscillation amplitude of the working container is: (10) Using the formula (10), we construct the amplitude-frequency characteristics of the oscillation system under study. In this case, we vary the ratio of m1/m2 (Figure 2) for a fixed value of the eccentricity е of the drive shaft; as well as the amplitude-frequency characteristics of the container of the vibrating massager when changing the eccentricity е at a fixed ratio m1/m2 (Figure 3).…”
Section: Sample Of Hammentioning
confidence: 99%
“…Domestic and foreign researchers, particularly, have shown that the proteolytic enzyme preparations of animal, vegetable, and microbial origin and own enzymes of the meat can affect the proteins and simultaneously increase the functional and technological properties of the raw materials as well as improve the organoleptic and structuralmechanical performance of the finished products [9]. An outstanding contribution to the development of the vibration technologies for implementing the mixing processes and uniform distribution of the components of the meat raw materials in the working volume, which is relevant to the technology under study, was made by wellknown domestic and foreign scientists [10]. To increase the energy potential of the executive bodies of mixing devices, it is advisable to use the auger and blade mixing elements [11].…”
Section: Introductionmentioning
confidence: 99%
“…У рибній промисловості важливу роль відіграє раціональне використання сировинної бази, оскільки на виробництво риба надходить із механічними пошкодженнями, різних розмірів, з дефектами. Технологія з виготовлення рибних формованих напівфабрикатів відкриває нові можливості в галузі раціонального використання вторинної рибної сировини, дає можливість розширити асортимент рибних продуктів (Ivaniuta et al, 2021).…”
Section: актуальністьunclassified